Ketidakpatuhan Pengkajian Resep pada Instalasi Farmasi Rawat Jalan Rumah Sakit X Jakarta (Journal of Hospital Management, 2019)
The issue of drug misconduct by pharmaceutical staff will harm and endanger patient safety. Pharmaceutical services guarantee safer drug use and reduce drug use errors. Thus, reliable health workers who have competence, knowledge, skills, and attitudes according to competency standards are needed to review prescriptions in order to guarantee the legality of prescriptions to minimize the incidence of drug errors.This study aims to provide empirical evidence of the influence of competence and compliance of prescription review by pharmaceutical staff on patient safety in the process of drug error events in outpatient pharmaceutical installations. The research method used is quantitative methods with the type of causality research. Data source is secondary. The unit of analysis is the pharmaceutical group. Horizon of time using one shot study. Data analysis using multinomial logistic regression analysis. The results showed that thecompetence and compliance of prescription assessments affected patient safety. There is a significant difference between the competence and compliance of prescription studies with the incidence of drug errors. The findings of the study are the high percentage of non-compliance performed by personnel with independent and supervised competence. Medium, the level of error is also caused by supervision competency. Keyword: competence, prescription review, medication errors, patient safety